Nanotechnology: An upcoming frontier in implant dentistry - Dipti Khullar; Nidhi Duggal; Sarabjit Kaur (Wolters Kluwer Medknow Publications, 2015)
Osseointegration, i.e., structural and functional union of the surface of dental implant with surrounding bone is paramount for the success of device. In recent years, osteogenesis at the bone-implant interface has been induced by structural modifications of the implant surface, particularly at the nanoscale level. This has been achieved through modulation of osteoblast adhesion. There is strong belief that nanoscale features in materials processing is truly a new frontier. This paper reviews recent advances in fabrication of novel coatings and nanopatterning of dental implants and their subsequent cellular interactions, leading to an improvement in osseointegration and hence the long-term clinical success of the "third dentition" i.e., dental implants.